Mobile learning approach in teaching elementary school English literation: What are their voices? - Puspa Dewi; Tusino Tusino; Titi Rokhayati; Ivan Ananta Luckita; Inna V Lisitsa (Universitas Sebelas Maret, 2025)
This study examines the impact of a mobile learning application on the reading and writing skills of fifth-grade students in Purworejo Regency, Central Java. Eighty students were divided into an experimental group using the LearnEnglish Kids: Playtime app and a control group using traditional methods. The data were collected through writing tests and questionnaires and anallyzed using Guttman scale Results showed significant improvement in the experimental group, with mean scores rising from 61.07 to 88.08 and 85% of students achieving an “Excellent” rating. The control group showed only modest gains, with mean scores increasing from 57.15 to 63.63. Tests for normality, homogeneity, and an independent sample t-test confirmed a statistically significant difference between the two groups (Sig. 0.000). Additionally, a questionnaire revealed that 71% of students agreed the app helped improve their language skills, and 96% felt it met their learning needs. These findings suggest that integrating mobile learning tools like LearnEnglish Kids: Playtime into the curriculum can significantly boost student performance and motivation. Future research should investigate the long-term effects of mobile learning on language skills and explore its applicability across different educational settings.